[Phylogeography and genetic structure of the species complex of the freshwater stingray, Potamotrygon orbignyi (Castelnau, 1855), among Amazonas and Orinoco rivers] (2017)
The freshwater stingray Potamotrygon orbignyi, is an important resource in the ornamental fish trade in South America. This group of rays is considered as part of a complex of species, due to its highly polychromatic dorsal pattern, its geographical differences in the sexual size of maturity and its great genetic variation. Taxonomic clarification is key to design and propose management actions for their populations. Phylogeny, species limits analysis and population structure were evaluated using mitochondrial DNA sequences (555pb COI and 398pb Cytb) and five nuclear microsatellites of 105 P. orbignyi along the Amazon rivers (n = 11) and Orinoco (n = 94). A calibrated phylogenetic tree based on Bayesian inference showed that the "species complex" of P. orbignyi is a polyphyletic group, and recovered two consistent clades (Clado-A and Clado-B). These clades are divided around 29Ma at the end of the Eocene. Ancestry relationships showed Clado-A as a sister species of P. motoro...